Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the quadratic equation [tex]\[ 2(x-7)^2 - 31 = 1 \][/tex] for [tex]\( x \)[/tex] in its simplest form, follow these steps:
### Step 1: Simplify the Equation
First, move the constant term on the right-hand side to the left-hand side by subtracting 1 from both sides:
[tex]\[ 2(x-7)^2 - 31 - 1 = 0 \][/tex]
This simplifies to:
[tex]\[ 2(x-7)^2 - 32 = 0 \][/tex]
### Step 2: Isolate the Squared Term
Add 32 to both sides to isolate the squared term:
[tex]\[ 2(x-7)^2 - 32 + 32 = 32 \][/tex]
[tex]\[ 2(x-7)^2 = 32 \][/tex]
### Step 3: Solve for the Squared Expression
Divide both sides by 2 to simplify further:
[tex]\[ \frac{2(x-7)^2}{2} = \frac{32}{2} \][/tex]
[tex]\[ (x-7)^2 = 16 \][/tex]
### Step 4: Solve for [tex]\( x-7 \)[/tex]
To solve for [tex]\( x \)[/tex], take the square root of both sides. Remember that taking the square root gives us two solutions, a positive and a negative root:
[tex]\[ x-7 = \pm \sqrt{16} \][/tex]
[tex]\[ x-7 = \pm 4 \][/tex]
### Step 5: Solve for [tex]\( x \)[/tex]
Now solve for [tex]\( x \)[/tex] in both cases:
1. [tex]\( x-7 = 4 \)[/tex]
[tex]\[ x = 4 + 7 \][/tex]
[tex]\[ x = 11 \][/tex]
2. [tex]\( x-7 = -4 \)[/tex]
[tex]\[ x = -4 + 7 \][/tex]
[tex]\[ x = 3 \][/tex]
### Solution
The solutions to the quadratic equation [tex]\( 2(x-7)^2 - 31 = 1 \)[/tex] are:
[tex]\[ x = 11 \quad \text{and} \quad x = 3 \][/tex]
In simplest form, the solutions are:
[tex]\[ \boxed{3 \text{ and } 11} \][/tex]
### Step 1: Simplify the Equation
First, move the constant term on the right-hand side to the left-hand side by subtracting 1 from both sides:
[tex]\[ 2(x-7)^2 - 31 - 1 = 0 \][/tex]
This simplifies to:
[tex]\[ 2(x-7)^2 - 32 = 0 \][/tex]
### Step 2: Isolate the Squared Term
Add 32 to both sides to isolate the squared term:
[tex]\[ 2(x-7)^2 - 32 + 32 = 32 \][/tex]
[tex]\[ 2(x-7)^2 = 32 \][/tex]
### Step 3: Solve for the Squared Expression
Divide both sides by 2 to simplify further:
[tex]\[ \frac{2(x-7)^2}{2} = \frac{32}{2} \][/tex]
[tex]\[ (x-7)^2 = 16 \][/tex]
### Step 4: Solve for [tex]\( x-7 \)[/tex]
To solve for [tex]\( x \)[/tex], take the square root of both sides. Remember that taking the square root gives us two solutions, a positive and a negative root:
[tex]\[ x-7 = \pm \sqrt{16} \][/tex]
[tex]\[ x-7 = \pm 4 \][/tex]
### Step 5: Solve for [tex]\( x \)[/tex]
Now solve for [tex]\( x \)[/tex] in both cases:
1. [tex]\( x-7 = 4 \)[/tex]
[tex]\[ x = 4 + 7 \][/tex]
[tex]\[ x = 11 \][/tex]
2. [tex]\( x-7 = -4 \)[/tex]
[tex]\[ x = -4 + 7 \][/tex]
[tex]\[ x = 3 \][/tex]
### Solution
The solutions to the quadratic equation [tex]\( 2(x-7)^2 - 31 = 1 \)[/tex] are:
[tex]\[ x = 11 \quad \text{and} \quad x = 3 \][/tex]
In simplest form, the solutions are:
[tex]\[ \boxed{3 \text{ and } 11} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.